Kebijakan Pemerintah Pidie Jaya dalam Pelestarian Tari Seudati untuk Pengembangan Pariwisata - Mujiburrahman, Mujiburrahman; Riski, Aflia; Meliza, Richa; Chalid, Ibrahim; Kamil, Ade Ikhsan (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2025)
This study examines the government policy of Pidie Jaya in preserving the traditional Seudati dance as a strategy for tourism development. The research focuses on how policy implementation addresses challenges arising from globalization, modernization, and declining public engagement, particularly among younger generations. Using a qualitative approach, data were collected through observation, interviews, and documentation involving government officials, artists, and local communities. The analysis also incorporated policy documents and case studies to evaluate the policy’s effectiveness. The findings reveal that current efforts have not yet produced optimal results in enhancing cultural awareness, tourism promotion, or local economic empowerment. Limited resources, weak monitoring mechanisms, and external cultural pressures remain significant obstacles. The study concludes that stronger financial support, systematic evaluation, and broader stakeholder participation are crucial to ensuring sustainable cultural preservation and tourism growth in Pidie Jaya.